Process automation instantiation for intelligence orchestration - Ramos, Edgar; Arumugam, Senthamiz Selvi (Frontiers in the Internet of Things, 2023)
Devices and use case heterogeneity in Internet of Things (IoT) make it challenging to streamline the creation of processes that orchestrate devices that work interactively through actuation and sensing (data generation and data processing) toward fulfilling a goal. This raises the question of what is needed to realize this vision using serverless technologies and leveraging semantic description tools that would eventually complement standards to describe such orchestration in a similar way to microservices (e.g., using TOSCA). This study analyzes the different requirements necessary in such automation description and tests them in some practical use cases in a particular application (vertical agriculture). It also provides a set of analyzed instructions that might be incorporated into a description language or become a definition format for an automation orchestration description to provide the necessary process deployment options and interaction chains between multiple devices and data sources. These instructions are analyzed by implementing an execution deployment engine from the intelligence orchestration concept. The practical utilization of such instructions is verified and tested with the use case.